Pelaksanaan Metode Karyawisata pada Pembelajaran Sejarah Kelas X IPS 2 di SMA Negeri 3 Bukittinggi - Utari Utari; Zafri Zafri (Jurusan Sejarah FIS UNP, 2020)
This research is motivated by the implementation of the field trip method by history subject teacher in Bukittinggi Senior High School, but there are still some steps in the field trip that are not yet in line with the theoretical field trip steps. This study aims to determine the appropriateness of the implementation of the field trip method carried out at Bukittinggi Senior high school by the history teacher with the theoretical field trip method steps. The subject of this research is the history teacher at Bukittinggi Senior High School. The method used in this study is an evaluative method with type of qualitative research. The results showed that in general the steps of the field trip had been carried out by the teacher well, but there weresome things that were not ideal, including : 1) the teacher had not clearly stated the purpose of the field trip method, this was related with conceptual skills not maximal from the teacher. 2) the teacher has not involved the child in determining the object of the field trip in the PjBL, This is caused by human skill factors that are applied by the teacher is still not optimal.